2021
DOI: 10.1002/cne.25210
|View full text |Cite
|
Sign up to set email alerts
|

Morphological properties of the axon initial segment‐like process ofAIIamacrine cells in the rat retina

Abstract: Signal processing within the retina is generally mediated by graded potentials, whereas output is conveyed by action potentials transmitted along optic nerve axons. Among retinal neurons, amacrine cells seem to be an exception to this general rule, as several types generate voltage-gated Na + (Na v ) channel-dependent action potentials. The AII, a narrow-field, bistratified axon-less amacrine cell found in mammalian retinas, displays a unique process that resembles an axon initial segment (AIS), with expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The peak density observed for the two retinas in our study (~5200 and ~4900 cells/mm 2 ) is somewhat lower than the peak densities reported for the two retinas analyzed by Wässle et al (1993; 7000 and 7500 cells/mm 2 , respectively). As suggested in a previous study from our laboratory (Liu et al, 2021), the difference could be due to the exact locations sampled, the extent of shrinkage, and age differences. Importantly, whereas the spatial density varies as a function of retinal region and eccentricity, with reduced density toward the periphery, the number of nearest neighbors stays essentially constant across the retina.…”
Section: Distribution Of Aii Amacrine Cells Across the Rat Retinamentioning
confidence: 68%
See 4 more Smart Citations
“…The peak density observed for the two retinas in our study (~5200 and ~4900 cells/mm 2 ) is somewhat lower than the peak densities reported for the two retinas analyzed by Wässle et al (1993; 7000 and 7500 cells/mm 2 , respectively). As suggested in a previous study from our laboratory (Liu et al, 2021), the difference could be due to the exact locations sampled, the extent of shrinkage, and age differences. Importantly, whereas the spatial density varies as a function of retinal region and eccentricity, with reduced density toward the periphery, the number of nearest neighbors stays essentially constant across the retina.…”
Section: Distribution Of Aii Amacrine Cells Across the Rat Retinamentioning
confidence: 68%
“…The characteristic thick apical dendrites of AII amacrine cells that descend vertically into the inner plexiform layer cannot be seen in the horizontal images and slabs illustrated in Fig. 1 , but were displayed in Liu et al ( 2021 ). The smaller and even more weakly labeled structures between the labeled cell bodies in Fig.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations